Research laboratory model of efficiency conversion optical radiation to electricity - Petrenko, A.; Skripnik, A.; Abramchuk, R.; Gorbatchevski, S. (Енергетика і автоматика, 2015)
Experimental study of optical radiation conversion efficiency of different light sources in electricity on the proposed academic laboratory bench using photovoltaic.